EFFECTIVENESS OF DIGITAL MEDIA IN SUPPORTING STUDENT-CENTERED LEARNING IN ELEMENTARY SCHOOL SCIENCE AND SOCIAL STUDIES (IPAS): A SYSTEMATIC LITERATURE REVIEW - Putu Renti Anggreni; I Gede Suwindia; Ni Nyoman Kurnia Wati (Universitas Islam Negeri Mataram, 2026)
This study is motivated by the shift from Teacher-Centered Learning (TCL) to Student-Centered Learning (SCL) in the digital era, particularly in Integrated Science and Social Studies (IPAS) learning at the elementary school level. The study aims to analyze the effectiveness of digital learning media in supporting the implementation of SCL in IPAS learning in elementary schools. The research employed a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) stages. Data were collected through article searches in Google Scholar, SINTA, and GARUDA databases with publication years ranging from 2020 to 2025. Of the 30 identified articles, 10 were selected for in-depth analysis based on the inclusion and exclusion criteria. The findings indicate that digital media such as interactive multimedia, Quizizz, Kahoot, Liveworksheet, Google Sites, and Interactive Flat Panel (IFP) are effective in improving students’ motivation to learn, active engagement, critical thinking skills, and understanding of IPAS concepts in elementary schools. Digital media also support the creation of more interactive, collaborative, contextual, and student-centered learning environments. However, the implementation of digital media still faces several challenges, including limited technological infrastructure, low teacher digital literacy, and the potential for digital fatigue among students. This study proposes a Strategic Digital SCL Framework integrating digital media, teacher competence, technology, learning activities, and student outcomes to strengthen Student-Centered Learning in elementary school IPAS instruction.